DISTINGSI PEMIKIRAN TASAWUF IBN ‘ATA’ILLAH AL-SAKANDARI - Abduloh Safik (IAIN Tulungagung, 2016)
Biography and writings of Ibn ‘At a’illah explained his expertise in the Maliki madhhab well as different patterns of thought Sufi mysticism with other Sufi figures. Therefore, Ibn ‘Ata’illah earned the nickname ahl al-hikmah. In addition he was a key member of the Order Shadhiliyah, Ibn ‘At a’illah classified prolific scholar who wrote the book. Not less than 20 works were born of his thoughts. His most famous work is Kitab al-Hikam. To make it easier to explore the thought of Ibn ‘At a’illah, need to understand first the development of his thinking. This paper seeks to ‘differentiate’ ideas of Sufism of Ibn ‘At a’illah with other Sufi figures.Keywords: Ibn ‘Atha’illah, Sufism, Ordo sufism